DETERMINISTIC CHARACTER OF CHANGES OF THE CASPIAN SEA LEVEL AND ITS QUANTITATIVE PARAMETERS - U. G. Magomedbekov (Юг России: экология, развитие, 2014)
Abstract. The results of determination of parameters of dynamics of Caspian Sea level changes were studied. We determined quantities and dimensions of the phase space and the attractor, we calculated exponents of Lyapunov and assessed value of Kolmogorov – Sinai entropy based on analysis of time series by the change in the reservoir for 1931–2009.Introduction. When interpreting the data on oscillatory phenomena an application of the theory of self-organization approaches becomes interesting, as it allows to set in a certain extent the behavior and evolution of the system regardless the nature of occurring in them processes.Methods. During the preparation of article we applied a complex approach of nonlinear dynamics, consisting of the use of the discrete Fourier transform, the reconstruction of the dynamics of the time series with the construction of phase portraits and determining the dimensions of the phase space and attractor, calculation of Lyapunov exponents and Kolmogorov – Sinai entropy.Results. It is found that Fourier spectrum–discrete; attractor dimension is expressed in non-integer number, and it is more than three; dimension of the phase space is equal to five; values of Lyapunov exponents correspond to: λ1> 0, λ2 = 0, λ3< 0; KS-entropy value is greater than zero (h = 0,018 ± 0,002); characteristic time that can be predicted by changes in the level corresponding to 58 - 60 days.Conclusion. The analysis conducted by methods of nonlinear dynamics shows deterministic character of Caspian Sea level changes for 1931–2009 and realization of dynamic chaos.